Application Of Additional Criminal Sanctions In The Form Of Restitution In Corruption Offences In Indonesia - Renghat Sinaga; H Abdul Razak Nasution (International Journal of Law, Crime and Justice, 2024)
One way to restore the lost state corruption is to impose additional punishment in the form of restitution payments. This effort provides results in the form of income to the state treasury from the payment of restitution. Of the several convicts who have been deposited the amount of restitution payments. Restitution as an additional punishment in corruption cases must be understood as part of the efforts to punish those who violate the law that is violated is a further act of corruption. Corruption has resulted in poverty so that the perpetrators of corruption must be sentenced to payment of restitution due to corruption that has occurred so far, in addition to harming state finances and the state economy, it also hampers the continuity of national development.The type of research conducted in the preparation of this research is normative juridical, which is viewed from the object of research is positive law that examines the rules of law governing criminal acts of corruption in an effort to prevent the prevention of criminal acts of corruption. The data obtained in this research will be analysed qualitatively in accordance with the specification of the nature of the research to examine between theory and practice in the form of criminal acts of corruption in an effort to prevent the prevention of criminal acts of corruption. Qualitative data analysis is to explore social facts not only on the surface but also to explore what actually happens behind the real events. Corruption that results in state financial losses in the concept of eradicating corruption is all expenditures or uses that are a burden on state finances where the expenditure or use of state money is based on unlawful acts, including reduced income or income to state finances based on unlawful acts, unlawful acts that result in state financial losses must be caused by acts that contain the nature of criminal law (wederrechtelijk). The imposition of restitution payments in the eradication of corruption as stipulated in Article 18 of the Law on the Eradication of Corruption is a means that can be applied to realise recovery efforts or recovery of state finances caused by corruption, restitution payments are imposed on the perpetrators of corruption in the amount of property obtained from corruption and the amount of property that has been transferred by the perpetrator to other parties where the other party is not prosecuted and does not commit acts against criminal law (wederrechtelijk).